Classroom Language Used by English Students in Microteaching Class - Sinta Hidayati; washlurachim safitri (Teaching English and Language Learning English Journal, 2022)
Classroom languages is language expressions used for communication between teacher and students in teaching learning process. Therefore the application of classroom language is important in teaching learning process for making habits in using English interaction in classroom. The aim of this study was to know about how the classroom language used by student teachers who took microteaching class and the most dominant categories of clasroom language used by student teachers. The design of this research was descriptive qualitative research, while the main instrument was the table analysis. The result showed that the classroom langauge used by student teachers was an excellent category with the total 92%, because the student teachers have been used 8 categories of classroom language. The most dominant categories of classroom language is simple intruction because easy to say and they have been made concept to teaching process. Keywords : Microteaching, Classsroom Language, Student Teachers